Molecular Design of Core Substituted Naphthalene Diimides for the Exfoliation of Graphite to Graphene in Chloroform. Issue 10 (8th August 2019) - Gharib, Desi H.; Lock, Peter; Moulton, Simon E.; Malherbe, Francois; Langford, Steven J.
Abstract: A significant challenge of liquid phase exfoliation (LPE) of graphite to yield graphene resides in the fact that most conventional solvents used are high boiling points and thus extremely difficult to eliminate, especially during processing of graphene into composites or films. Here, we advance the ability to produce high yield graphene in a low boiling point organic solvent, chloroform, using core‐substituted naphthalene diimides (cNDIs). Through the use of cNDIs it is possible to obtain high graphene concentrations of up to 0.13 mg/mL in chloroform. This yield represents a 69% improvement from graphene yields previously obtained in chloroform using unsubstituted NDIs. Characterisation of the products by UV‐Vis, X‐ray diffraction (XRD), Transmission electron microscopy (TEM), Raman spectroscopy and X‐ray photoelectron spectroscopy (XPS) support the use of cNDIs as an appropriate exfoliating agent in chloroform. Abstract : Graphene has been exfoliated in chloroform by using core‐substituted naphthalene diimides (cNDIs). High graphene yields of up to 0.13 mg/mL in chloroform can be achieved representing a 69% improvement from graphene yields previously obtained using unsubstituted NDIs.